A riddle in Ruby - Davis, Kent, 1970- (Greenwillow Books, an imprint of HarperCollins Publishers, 2016)
When Ruby Teach, thief-in-training, bungles a robbery that leaves her father captured, she must evade her pursuers, the Royal Navy and leaders of a secret society, to keep a secret, one she doesn't know.